Nuancing the "No build zone" in post Yolanda resettlements prospects and challenges in Estancia, Iloilo. - Enate, Chris Za Bea
The application of a no-build zone policy in coastal community areas affected by a disaster and the subsequent relocation of residents are met with controversy. In the Philippines the no-build zone policy proceeded from the pronouncement of the Office of the President in response to the devastating impact of Typhoon Yolanda and as a safety measure from future storm surges. The no-build zone was identitifed by the national government in accordance with the Water Code, which recommends a 40-meter buffer (no-build) zone from the average high tide mark. The decision to implement such a zone ultimately rested with the local government units (LGUs)., Using socio-logical system, this study examined the localization of the no-build zone policy by the Estancia, Iloilo local government as seen in post-Yolanda resettlements of two coastal communities, Brgy. Botongon and Brgy. Goco, Estancia. The study described the features, targets, and limitations of "No-Build Zone Policy" as drawn from 1976 Water Code, 1975 Revised Forestry Code and 1949 Civil Code of the Philippines. It also examined how the local governments' adoption of the no build zone informed the resettlement of the people in the two barangays.